Enhancing EFL Learning in Cameroon’s Language Centres through Content and Language Integrated Learning - Akumbu, Pius W.; Simo, Charlotte D. (Journal of English Language Teaching and Linguistics, 2018)
This study seeks to determine how Content and Language Integrated Learning (CLIL), already applied successfully in other parts of the world, could be adapted to teaching English as a foreign language in language centres in Cameroon. The problem identified was the fact that 43 out of 64 students leave language centres with a lot of general English but with little or no language abilities relevant to their fields of experience, whether academic or professional. The results revealed that the implementation of CLIL had a positive impact on learners’ development of diverse skills necessary for their success in academic and/or professional settings since there was a remarkable improvement in students’ performance in the experimental group (93%) as opposed to the limited (lower) performance of the control group (56.4%), providing therefore factual evidence of the effectiveness of the CLIL approach over other conventional approaches in meeting students’ needs and interests after training.